Storytelling about gender-responsive agricultural solutions: Training Guide - Metcalfe, J.; Gascoigne, T.; Cole, S.; Stirrat, M.; Gadeberg, Marianne (Econnect Communication, 2025)
Gender equality is high on sustainable development agendas. Yet in 2020, 62 percent of all bilateral aid remained ‘gender blind’. That same year, only 1 in 10 of more than 100,000 research papers on ending hunger considered gender differences in outcomes, and investments and evaluations of gender outcomes are still sorely lacking. Despite women’s significant contributions to agri-food systems, positive stories about women’s roles are few and far between in agri-food system discussions and media coverage. Dominating narratives often cast women as victims, entrench gender stereotypes and myths, and patronize or downright misrepresent their roles and contributions. In this way, the currently dominant narratives about women’s role in agri-food systems can be perceived as counterproductive, standing in the way of progress towards inclusive, equitable agri-food systems. Historically, in many cultures, stories were told around campfires to pass on lessons about life. They were a way of passing on knowledge at a time when many people could not read or write. The stories were dramatic and memorable, to engage the listener or reader. They were often repetitive. Storytelling—long lauded as one of the most powerful communications tools for influencing perceptions and actions—can be leveraged to reverse negative gender narratives by offering a persuasive vehicle for the evidence and experiences that can help readers and viewers understand rural women’s realities. Yet, the art of storytelling is rarely used to elevate and celebrate the experiences of rural women, despite its potential to effect greater focus, funding and research in support of more gender equality. As such, there is a pressing need to collect, produce and share ‘better’ stories about women in agri-food systems and agricultural solutions that work for women. Accordingly, in 2023 and through to 2025, the CGIAR GENDER Impact Platform organized three training programs, comprised of eight 2-hour modules, conducted partly virtually and (for the second training group) partly in person for a total of 45 science communicators from CGIAR and partners (as well as journalists) from around the world on how to prepare and publish stories on agricultural technologies that work for rural women. Mentoring was an essential component of ensuring the success of the training in delivering published stories. Econnect’s mentors worked individually with participants over three months of training to help them identify a story about a gender-responsive agricultural solution, organize their interviews and field trips, draft and edit their stories, and pitch their stories appropriately to their target publications. The training was based on a Theory of Change (table 1) which broadly assumes that greater capacity for telling positive, captivating, persuasive stories about women in agri-food systems will lead to more prolific and ‘better’ stories, which in turn will instil increased regard and expectations for development of gender-responsive agricultural solutions. This training resource guide was developed as part of this storytelling training series.